Mozzarella production with an addition of passion fruit (Passiflora edulis) juice - Pham, Thi Hoan (Journal of Technical Education Science, 2022)
This research aimed to evaluate the effect of passion fruit juice on the mozzarella properties, determine suitable temperature and rennet concentration for casein coagulation and evaluate some quality properties of mozzarella products. The analytical results showed that the passion fruit mozzarella (PM) made with 3% (v:v) passion fruit juice (PJ), rennet concentration of 0.025% (v:v) at coagulation temperature of 37 ℃ had the cheese yield efficiency of 9.47%, total solid content of 55.86% and cheese solid yield of 45.94%. Furthermore, the protein, lipid and dry matter contents of the PM samples were 24.10%, 21.30% and 52.20%, respectively. The microbiological analysis showed that harmful pathogens including Escherichia coli, Salmonella spp, Listeria monocytogenes, Staphylococci were not detected in the samples. The microstructure images of PM samples had many sharp edges in a form of clusters. Moreover, the average acceptance score of PM samples (6.8/9.0) was higher than that of the first reference sample (5.9) which used citric acid for acidification process and Emborg mozzarella (RS2) (6.0). Thus, adding passion fruit juice to the mozzarella making-process positively affected quality properties of final product, especially the sensory properties (sense of smell). Therefore, applications of passion fruit juice in the dairy product industry are potential.